Morphometric Characteristics of Polled Bali Cattle Calves as New Local Beef Cattle in Indonesia - Zulkharnaim Zulkharnaim; Syahdar Baba; Lellah Rahim; Muhammad Hatta; Renny Fatmyah Utamy; Hikmah M. Ali; Sri Hajriani (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2024)
This study aimed to determine the morphometric performance of polled Bali cattle aged 12-15 months and the influence of the cows on the morphometrics of breeding cattle.The research material consisted of 120 head Bali cattle divided into 40 head polled cattle, 40 head with horns, and 40 cows with horns. The study was conducted in Barru District, South Sulawesi Province. The study parameters consisted of withers height, body length, and heart girth. The data were statistically analyzed using the independent sample t-test, and the effect of the morphometrics of the cows on the calves was analyzed using simple regression analysis. Measurement data were analyzed using the IBM SPSS Statistics application. The results showed a very significant difference in the body length of polled and horned males (p<0.01). Significant differences were also found in withers height and body length between polled and horned female calves (p<0.01). Polled Bali cattle aged 12-15 months have a larger morphometric size than those with horns. It is hoped that identifying the superiority of polled Bali cattle will continue at different age statuses to compile information as material for the Indonesian National Standard for hornless Bali cattle.